Comparing data gathered in an online and a laboratory experiment using the trustlab platform - Nobuyuki Hanaki; Takayuki Hoshino; Kohei Kubota; Fabrice Murtin; Masao Ogaki; Fumio Ohtake; Naoko Okuyama (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This paper compares the results of an experiment conducted both in the laboratory and online with participants recruited from the same subject pool using the Trustlab platform. This platform has been used to obtain incentivized and internationally comparable behavioral economics measures of altruism, cooperation, reciprocity, trust, and trustworthiness, employing representative samples in many countries. We find no significant difference between the results from sessions conducted in the laboratory and online. While the existing literature shows that the choice between laboratory and online experiments can cause differences in results in some cases, our findings support the hypothesis that they do not cause differences in the behavioral economics measures when using the Trustlab platform.
Keywords: C90; 330; dictator game; trust game; public goods game